2006
DOI: 10.1111/j.1445-2197.2006.03906.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Venous Changes in Pneumoperitoneum During Laparoscopic Surgery

Abstract: The degree of intra-abdominal pressure affects the haemodynamics of the peripheral veins. Pneumoperitoneum during laparoscopy causes stasis in the peripheral veins. It is reasonable to use routine prophylaxis for deep vein thrombosis, in the light of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Gülec et al reported that laparoscopy can constrict the inferior vena cava leading to stasis in the peripheral veins and pooling of blood in the lower limbs [46]. In our cohort, 61% of the patients had laparoscopic surgery, which might influence the efficacy of whole body bioimpedance spectroscopy due the reduced urinary secretion, increased abdominal pressure and venous congestion in the lower limbs.…”
Section: Discussionmentioning
confidence: 76%
“…Gülec et al reported that laparoscopy can constrict the inferior vena cava leading to stasis in the peripheral veins and pooling of blood in the lower limbs [46]. In our cohort, 61% of the patients had laparoscopic surgery, which might influence the efficacy of whole body bioimpedance spectroscopy due the reduced urinary secretion, increased abdominal pressure and venous congestion in the lower limbs.…”
Section: Discussionmentioning
confidence: 76%
“…Pathophysiological factors that may lead to VTE following laparoscopic cholecystectomy include obstruction to venous outflow during surgical pneumoperitoneum and activation of the coagulation system. Decreased blood velocity or decreased venous outflow in the femoral veins during surgical CO 2 pneumoperitoneum was observed by several [22][23][24][25][26][27][28] but not all investigators. 29 Graded compression stockings reduced or abolished decreased blood velocity in one 26 but not in another investigation.…”
Section: Discussionmentioning
confidence: 98%
“…The increased IAP and reverse Trendelenburg position during laparoscopy have been shown to reduce femoral venous flow. 47,48 Nguyen et al 49 reported that increased IAP and reverse Trendelenburg positioning are independent factors that resulted in decreased femoral peak systolic velocity.…”
Section: Changes In Renal Functionmentioning
confidence: 99%